A Study ou Removal of Cyanide from Wastewater Using Ion Exchange - Yaacob, Mohd Yussof (Universiti Teknologi Petronas, 2004)
Sewage is the wastewater released by residences, businesses and industries in a community. It contains 99.94 percent water, with only 0.06 percent of the wastewater dissolved and suspended solid material. Biochemical Oxygen Demand (BODs) is used as a standard for the strength measurement of the wastewater.